Кристаллохимический фактор прочности удержания радиогенного 187Os в структуре рениеносных молибденитов - Вальтер, А.А.; Писанский, А.И.; Подберезская, Н.В. (Видавничий дім "Академперіодика" НАН України, 2007)
To understand the possible cause of the strong keeping of radiogenic Os in comparison with initial Re in the molybdenite structure, we compare the cation positions in MoS2, ReS2, and OsS2 and the geometry of “empty” octahedra of the molybdenite structure. The similarity of
“empty” octahedra of MoS2 and the Os environment in OsS2 is determined. So, one can assume that knock-on atoms of 187Os can be fixed in “empty” octahedra by recoiling or the later thermal action.